The Level Of Psychological Resilience In a Sample Of The Elderly Residents at Infirmaries- Field Study In City OF Latakia - - Sobh, Safaa; Sady, Rima; Bekdash, Raneem (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This research aimed to know the level of a Psychological Resilience among the elderly residents at infirmaries, and to know the differences in the degree of Psychological Resilience between males and females, as it aimed to detect the differences in the level of a sense of a Psychological Resilience depending on the variables; of social situation, and age. In This research it is used Psychological Resilience scale of preparation by the researcher. The researcher extracted the validity and reliability for the scale of Loneliness. The scale is applied in social care homes in the cities of Latakia. The sample consisted of (57) elderly 32 males and 25 female. The research is found the following results: The level of a Psychological Resilience is average, and there is no statistically significant differences in the degree of Psychological Resilience between males and females, as too there are no statistically significant differences depending on the variables of the time they spent at Infirmaries, While there are statistically significant differences in the level of a Psychological Resilience depending on the variables of the social situation.